Snake venom L-Amino Acid Oxidases and their potential biomedical applications - Tan, N.H.; Fung, S.Y. (2008)
L-amino acid oxidase (LAAO) occurs widely in snake venoms. The enzyme is highly specific for L-amino acids, and generally hydrophobic amino acids are the best substrates. LAAO is a flavoprotein consisting of two identical subunits, each with a molecular mass of approximately 60 kDa. The purified enzymes are glycoproteins with 3-4 carbohydrate. Deglycosylation of the enzyme did not alter the enzymatic activity but appeared to alter its pharmacological activities. The amino acid sequences of snake venom LAAOs showed a high degree of homology. X-ray structural analysis of LAAO revealed a dynamic active site and the presence of 3 domains: a FAD-binding domain, a substrate-binding domain and a helical domain. LAAOs were reported to exhibit moderate lethal toxicity. Recent studies showed that LAAOs are multifunctional enzymes exhibiting edema-inducing, platelet aggregation inducing or inhibiting, apoptotic inducing as well as anti-bacterial, anti-coagulant and anti-HIV effects. These effects are mostly mediated by the H2O2 liberated in the oxidation process but direct interactions between LAAO and the target cells may play an important role. High resolution X-ray structure of the enzyme revealed the presence of a channel that would direct the H2O2 product to the exterior surface of the protein, near the glycan moiety at Asn 172. The glycan moiety was thought to be involved with LAAO-target cell interaction. This may explain the ability of LAAO to localize H2O2 to the targeted cells. A better understanding of the pharmacological actions of LAAOs will facilitate the application of snake venom LAAOs in the design of anti-cancer and anti-HIV drugs as well as drugs for the treatment of infectious diseases caused by parasites such as leishmaniasis.